2013
DOI: 10.1080/15583724.2013.806544
|View full text |Cite
|
Sign up to set email alerts
|

Electrically Conducting Polymer-Based Nanofibrous Scaffolds for Tissue Engineering Applications

Abstract: Conducting polymers are attractive biomaterials for tissue engineering applications as they can deliver electrical signals to cells for the regeneration of injured tissues. To make conducting materials relevant and effective as tissue engineering scaffolds, incorporation of three-dimensional features and contact guidance cues into conducting polymers would be desirable. Recent studies have demonstrated the development of conducting nanofibrous scaffolds, which can simultaneously provide both electrical and top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 80 publications
0
23
0
Order By: Relevance
“…The human body is a complex electrical system that can be most noticeably observed in the action potentials that are integral to the regulatory mechanisms in muscles and nerves. Furthermore, these biological electrical fields-apart from being crucial in the function of tissues such as the heart, muscles, and nerves-have a significant role in cellular behaviour including proliferation, morphology, signalling, migration, orientation, and regenerative processes [1][2][3][4][5][6][7][8]. Subsequently, electrical stimulation techniques and electroactive materials have been developed within tissue engineering in order to modulate cellular responses and enhance tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The human body is a complex electrical system that can be most noticeably observed in the action potentials that are integral to the regulatory mechanisms in muscles and nerves. Furthermore, these biological electrical fields-apart from being crucial in the function of tissues such as the heart, muscles, and nerves-have a significant role in cellular behaviour including proliferation, morphology, signalling, migration, orientation, and regenerative processes [1][2][3][4][5][6][7][8]. Subsequently, electrical stimulation techniques and electroactive materials have been developed within tissue engineering in order to modulate cellular responses and enhance tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Electroactive scaffolds can be fabricated from conductive materials or prepared by the addition of conductive fillers to create a composite. These conductive materials can be classified as: carbon-based [5,12,14,15], conductive polymers [1][2][3]6], and metallic-based [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] Amongst the many classes of CPs, polypyrrole has been widely utilized in various bioelectronics applications for its high electrical conductivity, biocompatibility, and stability under atmospheric conditions and elevated temperatures. [13,14] Despite the many advantages of using polypyrrole for bioelectronics and bioengineering applications, [15][16][17] their insolubility limits their processability for large-area fabrication of organic and bioelectronic devices. [18] Their poor solubility can be attributed to the strong inter-and intra-molecular interactions between the polypyrrole chains and the tendency to crosslink during polymerization.…”
Section: Doi: 101002/marc201800749mentioning
confidence: 99%
“…[41][42][43][44][45][46][47][48][49] Schmidt and Langer showed that ES of PC12 cells on polypyrrole increased the number and length of neurite outgrowths from the cells. [50] Various groups have shown that Schwann cells adhere to polypyrrole-based materials, [51][52][53][54][55] and that DRG adhere to polypyrrole-based [51,56,57] or poly(3,4-ethylenedioxythiophene)-based materials. [56] Flexible tube-like peripheral nerve conduits composed of polypyrrole and silicone were shown to be nontoxic and non-immunogenic in vivo in rats, [51] and axons can grow into tube-like peripheral nerve conduits composed of poly(D,L-lactide-co-ε-caprolactone).…”
Section: Introductionmentioning
confidence: 99%